Simulation and Optimization of Municipal Solid Waste Incineration for Energy Recovery in Maiduguri, Borno State, Nigeria. - Tela, B. M.; Oumarou, M. B.; Eljummah, A. M.; Ngala, G. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This paper presents an analysis, modelling and simulation of Maiduguri municipal solid waste powered electricity generation plant using ANSYS. Determination of the waste’s combustion characteristics: physical, proximate and ultimate analyses using ASTM standard was carried out. Initial and boundary conditions were applied in respect of the materials and geometry in order to carry out a numerical calculation. The reduced scale physical model batch type MSW power generating plant was successfully constructed for use to validate the CFD analysis. The MSW was sorted, graded, sized and weighted before being fed into the designed batch type model incinerator to fire the boiler. The temperature and pressure of the steam generated were measured using digital thermocouples and pressure gauges so as to quantify the expected energy. A comparison of the simulated and experimental temperature results showed that while Area A had 1090. K, 1409.9 K and 1609.6 K, Area B had 1918.1 K, 1893.6 K and 1425.1 K, Area C had 1413.1 K, 1548.8 K and 1036.6 K during simulation against an average of 1641.9 K for Area A, an average of 1896.3 K for Area B and lastly for Area C, an average of 1641.9 K, using the batch type MSW incinerator. The R2 value of 0.979 was observed for 5 kg load, 0.994 for 4 kg load and 0.999 for 3 kg load, for Area A. For Area B, the R2 values range from: 0.992, 0.993 and 0.995 for 5 kg, 4 kg and 3 kg respectively. For Area C, the R2 values range from: 0.998 for 5 kg, 0.996 for 4 kg and 0.987 for 3 kg. The constructed municipal solid waste power plant generated 6.4 V, 6.6 V and 6.5 V for Area A, B and C respectively for 33 minutes. A mathematical equation for the calorific value was developed using ANSYS, Ms Excel and was found to compare favourably, for up to 87.5% with the Model, and 87.40% when compared to the Dulong Berthelot’s formula. The moisture content, the feed rate and the energy content of the MSW greatly affect the quantity of electricity generated from the municipal solid wastes of Maiduguri.